Pengaruh Terapi Relaksasi Dzikir Terhadap Tingkat Kecemasan Pada Lansia Hipertensi Di Puskesmas Air Tawar Kota Padang Tahun 2022 - Rika Syafitri; Erni Musmiler; Heri Budianto (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2022)
Probability More and more, many people experience anxiety which will cause the elderly to be susceptible to hypertensive disorders. Anxiety has a range of adaptive responses to maladaptive. Purpose of this study to analyze The Effect Of Dhikr Relaxation Therapy On Anxiety Level To Hypertension Of Elderly Methode Research design of this study was pre- experiment one group pre test post test design. The population were all elderly hypertension at Elderly Posyandu , 594 people. The sampling technique used simple random sampling with a sample of 19 people. The instrument of the research used the DASS (Deperession Anxiety Stress Scale) questionnaire with data processing editing, coding, scoring, tabulating and statistical test using Wilcoxon with a <0.05. Resulth The results of the study most (65.6%) respondents had level of anxiety in elderly hypertension before dhikr relaxation therapy were 19 people while the majority (53.1%) respondents had level of anxiety in elderly hypertension after dhikr relaxation therapy was normal at 13 people. Wilcoxon test showed that significant value r = 0,000 <a (0,05), so H1 was accepted. Conclution This research can be concluded that there is The Effect Of Dhikr Relaxation Therapy On Anxiety Level To Hypertension Of Elderly